Andean region: a shapefile of Morrone’s (2015) biogeographical regionalisation - Löwenberg-Neto, Peter (Zootaxa, 2015)
Morrone’s (2015) biogeographic regionalisation of the Andean region is based on the distributional ranges of terrestrial plants and animals. It is the most comprehensive and methodologically supported biogeographical scheme for the region to date. The Andean region comprises one transition zone (the South American transition zone), three subregions (Central Chilean, Subantarctic and Patagonian) and 15 provinces (Morrone, 2015).